Cohesion and cohesion mechanisms in the composition of texts - Evangelista Huari, Desiderio (2014)
In the teaching of writing and composition of texts, what to teach?, what to teach for?, how to teach? are recurring questions what a lot of teachers make to themselves about this area, specially when they work at the university. Therefore, these unanswered questions are related to what topic professors teach and what methodological strategies they use. Exactly for that reason, the content of the current article is part of the sixth chapter of the research which I made for my Ph.D. thesis and whose original title is Syntactic strategies to improve the text coherence and cohesion in the universities students’ wordings. As we know, cohesion is the grammatical characteristic which  all  the  text  show to  ensure the link between two components. For that purpose, we use some  elements called mechanism cohesion. These cohesion elements are related between the referents, that being so, anaphoric or cataphoric character which we detail in  this article.